Non-specific resistance and specific immunogenesis of the body of the bird cross Loman Brown on the background of biostimulation. Issue 1 (January 2020) - Tyurin, V; Semenov, V; Kozak, S; Ivanov, N; Koshich, O; Tikhonova, G; Lyagina, E
Abstract: PV-1 immunostimulant influence on the parameters of non-specific resistance and specific immunogenesis of bird cross Loman Brown is discussed in the paper. It was established experimentally that feeding chickens by the PV-1 preparation in doses of 0.05 ml/kg, 0.10 and 0.15 ml/kg of body weight, respectively, once a day within 10 days with a 10-day break, with repeating cycles up to 111-day of their age, stimulates the growth and development of young. Immunization of a bird against the background of the use of the immunotropic drug PV-1 is accompanied by an increase in immunity: when chickens are vaccinated against Gumboro disease, the titers of specific antibodies are increased by 53.3%, against Newcastle's disease - by 50.0% and against egg drop syndrome-76 - by 26.5%. An increase in the egg productivity of laying hens grown on the background of the use of PV-1 was established: egg production for the initial hen increased by 9.2 - 17.8%, egg weight - by 0.5 - 4.6%. Studying the meat productivity of poultry grown on the background of the use of the PV-1 preparation, an increase in the slaughter yield of 1.7–5.0% was established, the yield of edible parts increased by 6 ±3.20 – 155±3.40 g (P <0.001).